Neutron matter instabilities induced by strong magnetic fields - Aguirre, Ricardo Miguel (2013)
We study some properties of spin-polarized neutron matter in the presence of a strong magnetic field at finite temperature. Using the Skyrme model together with the Hartree-Fock approximation we obtain an energy density functional that is employed to extract the spin polarization, the effective mass and the magnetic free energy of the system. In order to find the equilibrium state, we have analyzed different global spin configurations over a wide range of matter density (0<n/n0≦3), magnetic field intensity (1014 G≦B<1019 G) and temperature (T≦80MeV). The outcome is that the system can be either completely spin-down polarized or partially polarized. A change in any of the (n, T, B)-variables can induce a transition from one polarization state to the other. The transition takes place in a surface in the (n, T, B)-phase space, which represents an instability of the system. We have also found a discontinuity in the internal energy associated with this change in the state of magnetization.